Smart, Connected, and Portable Biosensors and Bioelectronics for Advancing Human Healthcare, Disease Diagnosis, and Therapeutics (MDPI - Multidisciplinary Digital Publishing Institute, 2023)
Research and development related to smart, connected, and portable biosensors and bioelectronics have been game changing in the fields of diagnostics and health management. Unlike conventional biosensors, these devices allow rapid, accurate, and on-site detection of biomarkers, which helps to prevent disease spread by the source control. This reprint contains experimental/computational studies and systematic reviews that report advances towards addressing current challenges and the future scope of the field of portable biosensors and bioelectronics.